CHARACTERISTICS AND MANAGEMENT OF MYOPIC TRACTION MACULOPATHY IN MYOPIC EYES WITH AXIAL LENGTH LESS THAN 26.5 mm. Issue 3 (March 2022) - Chen, Jing; Chen, Shida; Zhao, Xiujuan; Lian, PING; Yu, Xiling; Huang, Xia; Liu, Bingqian; Li, Yonghao; Lu, Lin
Abstract : Purpose: To explore the characteristics and underlying mechanisms of myopic traction maculopathy (MTM) with axial length less than 26.5 mm and to assess the effectiveness of macular buckling for the treatment of MTM. Methods: Thirty-eight MTM eyes with axial length less than 26.5 mm were prospectively enrolled. Thirty-one eyes received surgery, and they were followed up for at least 6 months. Characteristics of MTM and surgical outcomes were evaluated. Results: Of the MTM eyes, 92.11% (35/38) showed posterior staphyloma. Narrow macular staphyloma was the most common type (54.29%, 19/35), followed by peripapillary (37.14%, 13/35). Three cases (8.57%) had wide macular staphyloma, and 44.74% of cases (17/38) had vitreoretinal traction. Twenty-two MTM eyes of type T3 underwent macular buckling surgery, and all the cases achieved foveal reattachment after the surgery. The mean best-corrected visual acuity improved significantly at the 6-month follow-up ( P < 0.001). Nine MTM eyes of type T4 or T5 received combined surgery, all macular holes recovered, and the best-corrected visual acuity also improved postoperatively ( P = 0.008) as of the 6-month visit. Conclusion: Posterior staphyloma might serve as the initial force of the pathogenesis of MTM in eyes with axial length <26.5 mm. Macular buckling is a productive way to improve the MTM.